2022
DOI: 10.1016/j.pharma.2021.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on drug-related problems and pharmacist interventions in geriatric acute care units

Abstract: Objectives : To assess and compare the pharmaceutical analysis on drug management in a geriatric acute care unit prior to and during the COVID-19 pandemic. Methods : This was a single-centre, retrospective, and comparative cohort study. All Pharmacist Interventions (PIs) carried out in the unit between 27 January 2020 and 30 April 2020 were distinguished according to whether they were conducted prior to or during the first wave of COVID-19. The main outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Penicillin, followed by macrolides, were the most commonly identified antimicrobials. Also, in a study from an acute geriatric unit analyzing a total of 355 patients before and during the first COVID-19 wave, DRP were concluded to be mostly related to anti-infectious drugs during the pandemic (20.3%, p = 0.038) ( M. Chappea, M. Corvaisier, A. Brangier, C. Annweiler, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penicillin, followed by macrolides, were the most commonly identified antimicrobials. Also, in a study from an acute geriatric unit analyzing a total of 355 patients before and during the first COVID-19 wave, DRP were concluded to be mostly related to anti-infectious drugs during the pandemic (20.3%, p = 0.038) ( M. Chappea, M. Corvaisier, A. Brangier, C. Annweiler, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study performed by Chappea et al, 2022 , compared DRP identified prior to and during the first wave of COVID-19. Even they included less number of patients, this group found a higher proportion of pharmaceutical interventions during pandemic.…”
Section: Discussionmentioning
confidence: 99%